Update of the EPTN atlas for CT- and MR-based contouring in Neuro-Oncology - Eekers, Daniëlle B P; Di Perri, Dario; Roelofs, Erik; Postma, Alida; Dijkstra, Jeanette; Ajithkumar, Thankamma; Alapetite, Claire; Blomstrand, Malin; Burnet, Neil G; Calugaru, Valentin; Compter, Inge; Coremans, Ida E M; et al. (Radiotherapy and oncology, 2021)
BACKGROUND AND PURPOSE: To update the digital online atlas for organs at risk (OARs) delineation in neuro-oncology based on high-quality computed tomography (CT) and magnetic resonance (MR) imaging with new OARs. MATERIALS AND METHODS: In this planned update of the neurological contouring atlas published in 2018, ten new clinically relevant OARs were included, after thorough discussion between experienced neuro-radiation oncologists (RTOs) representing 30 European radiotherapy-oncology institutes. Inclusion was based on daily practice and research requirements. Consensus was reached for the delineation after critical review. Contouring was performed on registered CT with intravenous (IV) contrast (soft tissue & bone window setting) and 3 Tesla (T) MRI (T1 with gadolinium & T2 FLAIR) images of one patient (1 mm slices). For illustration purposes, delineation on a 7 T MRI without IV contrast from a healthy volunteer was added. OARs were delineated by three experienced RTOs and a neuroradiologist based on the relevant literature. RESULTS: The presented update of the neurological contouring atlas was reviewed and approved by 28 experts in the field. The atlas is available online and includes in total 25 OARs relevant to neuro-oncology, contoured on CT and MRI T1 and FLAIR (3 T & 7 T). Three-dimensional (3D) rendered films are also available online. CONCLUSION: In order to further decrease inter- and intra-observer OAR delineation variability in the field of neuro-oncology, we propose the use of this contouring atlas in photon and particle therapy, in clinical practice and in the research setting. The updated atlas is freely available on www.cancerdata.org.
Keywords: magnetická rezonanční tomografie; Magnetic Resonance Imaging; Brain; Organs at Risk; European Particle Therapy Network; Organs at risk; kritické orgány; Humans; Particle therapy; počítačová rentgenová tomografie; Radiotherapy Planning, Computer-Assisted; Radiotherapy; radiační onkologie; Radiation Oncology; Atlas for neuro-oncology; Tomography, X-Ray Computed; lidé; plánování radioterapie pomocí počítače